2020
DOI: 10.1177/1077801220969901
|View full text |Cite
|
Sign up to set email alerts
|

Combat Workplace Sexual Harassment by Third Parties? Reframing Institutional Measures and Cultural Transformation in South Korea

Abstract: This study investigated the risk factors for workplace sexual harassment in South Korea using cross-sectional data of the 2014 and 2017 Korean Working Conditions Survey (KWCS). A generalized linear model specified with a Poisson distribution and log link function was performed. Females, younger adults, jobs in services or sales, tasks that involve visiting places where clients reside, and significant work time contribution to customers were associated with increased gender harassment and unwanted sexual attent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…Our study rea rms that bullying harassment remains a serious threat to safe and healthy working conditions for working Americans [25]. We also con rmed that gender matters when it comes to mental health issues [38].…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Our study rea rms that bullying harassment remains a serious threat to safe and healthy working conditions for working Americans [25]. We also con rmed that gender matters when it comes to mental health issues [38].…”
Section: Discussionsupporting
confidence: 62%
“…Job-related characteristics were included based on the uni ed model [25]. Participants were asked, "Please tell me whether you strongly agree, agree, disagree, or strongly disagree with this statement?…”
Section: Additional Covariatesmentioning
confidence: 99%
See 1 more Smart Citation
“…One alternative conceptualization of the construct of sexual harassment treats it as a somewhat subjective phenomenon [27], with the argument that people who have experienced the same conditions can reach different conclusions about whether sexual harassment has occurred; indeed, a primary factor in that conceptualization is whether victims themselves perceive that they have been sexually harassed. However, in the hotel industry, the challenge appears to be how seriously harassment is taken even when it is clear: Hotel employees had reported that even when they were clear that they were being sexually harassed, they just ignored it or accepted it as part of their work [7,8]; other researchers documented, though, that these responses were significantly affected by personal characteristics, specific occupational and environmental aspects, and gender differences [28,29]. Nevertheless, irrespective of public or victim perceptions of its seriousness, sexual harassment in the hotel industry is an overt sexual offense and a phenomenon that cannot be overlooked [5][6][7][8]26].…”
Section: Introductionmentioning
confidence: 99%
“…H. Kim, Choo, & Lee, 2017; Kwon et al, 2016) or suffer from the unhelpful or hurtful responses (Ahrens, Cabral, & Abeling, 2009; Heo & Jo, 2012; M. J. Kim, 2015; J. H. Lee, 2008; Ullman & Peter-Hagene, 2014).…”
mentioning
confidence: 99%